Oxidative Coupling of Methane Over (CaO + ZrO2) Modified with Sodium Ion - Dayyani, Nahid; Piri, Somayyeh; Yousefi, Mohammad; Piri, Farideh (Asian Journal of Chemistry, 2010)
Oxidative coupling of methane was carried out over various metal oxide catalysts (CaO + ZrO4) modified with NaCl, NaI and NaOH and the catalytic performance of the catalysts was examined. These catalyst, which was prepared by sol-gel and then mixed of [Zr(OH)4 + Ca(OH)2] with an aqueous solution of NaCl and NaOH, was the most effective for the formation of ethene and ethane among all the catalysts tested in this study. The results shows that the surface concentration of Na+ species on each series of catalysts are related to electronegativity of counter ion with Na+.